Does board independence moderate the relationship between environmental disclosure quality and performance? Evidence from static and dynamic panel data. Issue 3 (3rd June 2019) - Alipour, Mohammad; Ghanbari, Mehrdad; Jamshidinavid, Babak; Taherabadi, Aliasghar
Abstract : Purpose: This study aims to link environmental disclosure quality (EDQ) to firm performance and examine the moderating role of board independence in this relationship. Design/methodology/approach: Drawing on agency theory and stakeholder theory, the authors developed and tested hypotheses using original survey data from 720 firm-year observations collected from 120 Iranian companies over six years between 2011 and 2016. In this paper, they conducted static and dynamic panel data analysis. Findings: After correcting for endogeneity bias, the results showed that there is a significant positive relationship between EDQ and firm performance. The results also showed that board independence significantly reinforces the positive effect of EDQ on performance, and firms with more independent board members are involved environmental disclosure for improved performance. This is consistent with agency theory, which posits that a more independent board of directors can better monitor the CEO and reduce incentives for pursuing personal interests, which in turn improves performance. The results are robust after performing sensitivity tests. Research limitations/implications: This paper takes the perspective of corporate governance to empirically examine the effect of EDQ on firm performance. This study makes a contribution to the literature by showing that board independence moderates the effects of EDQ on firm performance. Practical implications: The evidence supports the emphasis that recent policy statements have put on increasing the number of independent directors on corporate boards. This study offers insights to policymakers interested in enhancing the monitoring role of corporate boards. Originality/value: The study adds value to the understanding of the effect of the EDQ on performance and how board independence influences this relationship, particularly in an emerging economy like Iran.